From sustainable tourism to smart sustainable cities: perceptual mapping of gen Y and gen Z residents / Aijaz Ahmad Khaki, Annum Makhdoomi and Mudasir Ahmad Mir - Ahmad Khaki, Aijaz; Makhdoomi, Annum; Ahmad Mir, Mudasir (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
This paper examines the intricate dynamics that shape the relationship between sustainable tourism and the development of smart sustainable cities, while also analysing generational disparities. The study employs a multidimensional perspective, where sustainable tourism is defined by five dimensions - economic, social, cultural, environmental, and technological - and smart sustainable cities are characterized across four dimensions - planning, environmental, social, and smart. To comprehensively assess the impact of sustainable tourism on smart sustainable cities, as perceived by residents, a combination of primary and secondary data is utilized. The primary data was collected through selfadministered questionnaires which were distributed among 394 residents in Kashmir, capturing the perspectives of residents from Generations Y and Z. To test the hypotheses, Structural Equation Modelling (SEM) is employed utilizing the SPSS AMOS software. The results indicate a significant relationship between the implementation of sustainable tourism practices and the development of sustainable smart cities.